CENPRIS USM TO HOLD PUBLIC FORUM ON NONVIOLENT ALTERNATIVES IN DEALING WITH EXTREMISM - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 8 September 2016 – The Universiti Sains Malaysia (USM) Centre for Policy Research and International Studies (CENPRIS) will be organising a public forum on the topic of “Violent Extremism: Islam and Nonviolent Policy Alternatives” on 21 September, 2016 at the Equatorial Hotel in Bukit Jambul, Penang.